Contribution of Boll Mass and Boll Number to Irrigated Cotton Yield - Sharma, Bablu; Mills, Cory I.; Snowden, Chase; Ritchie, Glen L. (Agronomy journal, 2015)
The production of fruit on upland cotton (Gossypium hirsutum L.) varies with environment, cultivar, and management practices, including irrigation. Yield increase in response to irrigation is a combination of additional boll production on the plant and differences in the size of individual bolls. Previous research on this subject is incomplete. The purpose of this research was to compare the effects of irrigation on boll distribution and boll size in four cotton cultivars in West Texas. Boll distribution and boll mass in response to 10 daily irrigation levels (0–6.5 mm d−1) were compared among four cultivars with varying maturities [‘Deltapine 1212 B2RF’ (DP1212), ‘Deltapine 1219 B2RF’ (DP1219), ‘FiberMax 2484 B2F’ (FM2484), and ‘FiberMax 2011 GT’ (FM2011)] from 2011 to 2013 in Lubbock, TX. Boll production and retention followed cultivar‐specific patterns in all 3 yr. Two cultivars (DP1212 and FM2011) produced fruit primarily at the bottom and middle of the plant, one had increased production high on the plant (DP1219), and one produced fruit almost exclusively in the middle of the plant (FM2484). Both boll number and boll mass contributed to lint yield, with boll number being the major determinant (on average, 90%) of lint yield, whereas boll mass accounted for 10% of lint yield on average. The contribution of boll number and boll size to yield varied among cultivars and did not appear to be wholly maturity‐related. Research studies focused on boll number should be aware that boll distribution does not account for all of the variation in yield.